2019
DOI: 10.3389/fpsyg.2019.02688
|View full text |Cite
|
Sign up to set email alerts
|

The Computational Boundary of a “Self”: Developmental Bioelectricity Drives Multicellularity and Scale-Free Cognition

Abstract: All epistemic agents physically consist of parts that must somehow comprise an integrated cognitive self. Biological individuals consist of subunits (organs, cells, and molecular networks) that are themselves complex and competent in their own native contexts. How do coherent biological Individuals result from the activity of smaller sub-agents? To understand the evolution and function of metazoan creatures' bodies and minds, it is essential to conceptually explore the origin of multicellularity and the scalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
234
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 165 publications
(235 citation statements)
references
References 293 publications
(288 reference statements)
1
234
0
Order By: Relevance
“…If complexity is a measure of problem-solving capacity, then to some degree the opposites are true. An organism or system "complexifies" over time when it faces challenges, opportunities, or environments that it is ill equipped to handle [134][135][136]. With greater complexity come new options, additional flexibility, and expanded information processing.…”
Section: Organizing Principlesmentioning
confidence: 99%
“…If complexity is a measure of problem-solving capacity, then to some degree the opposites are true. An organism or system "complexifies" over time when it faces challenges, opportunities, or environments that it is ill equipped to handle [134][135][136]. With greater complexity come new options, additional flexibility, and expanded information processing.…”
Section: Organizing Principlesmentioning
confidence: 99%
“…Quantitative morphological analysis and an unbiased machine-learning approach revealed that this capability included significant distance in both time and space: small pieces of Physarum were able to detect the presence of objects at a distance of several centimeters, and decide which way to go hours before actually moving in that direction. This reveals a minimum bound on the spatio-temporal boundary of the basal cognition of this organism (Levin, 2019).…”
Section: Discussionmentioning
confidence: 79%
“…The "cells" in these models are Bayesian agents employing active inference (Friston, 2010;; they have both long-term (genetic) and short-term (cellular state) memories, inferential and communication capabilities, and the ability to modify their local microenvironment by moving in space relative to the other cells. They therefore exhibit a kind of "basal cognition" (Baluška and Levin, 2016;Levin, 2019) in the sense of systems that exhibit memories and make decisions about possible outcomes in a contextspecific manner. In these models, communication is cooperative: the cells do not withhold information, provide misinformation, manipulate each other's information processing, or send signals telling other cells to stop dividing or die.…”
Section: Building a Body Is Building An Environmentmentioning
confidence: 99%